Content Validity Of The Islamic Emotional Regulation Module - Mohd Izwan Mahmud; Joki Perdani Sawai; Masturina Mahazir; Shamsuritawati Sharif; Rezki Perdani Sawai (Human Resource Management Academic Research Society, 2024)
Indexed by ERA